OSTEOLOGICAL STUDIES of PIGS of POLTAVA MEAT BREED BY USING THE DIFFERENT TECHNOLOGIES OF SOY FEED PREPARATION - Чухліб, Є. В.; Голуб, Н. Д.; Скареднов, Д. Ю. (Scientific Progress & Innovations, 2015)
The results of pigs’ fattening of Poltava meat breed using soy feed, which made by different technologies (expundation under pressure, spin under pressure, extrusion) and the impact of these protein feeds on the chemical composition and strength of the femoral bone. More productive pigs were fed soy concentrate (Group R1), soybean oilcake (group R2) and soy extrudate (group R3). In feeding they showed average growth 825–833–785 g, and spent 3,26–3,47 feed units for 1 kg of growth. Their femoral bone had more calcium to 1,66–1,04–2,78 % and phosphorus to 0,67–0,53–0,38 % than the bones of animals in the control group. Piglets of the research groups had smaller diameter of bone to 0,51–0,33–0,73 mm, but thicker thickness of bone’s wall (except group R2) to 0,35–0,24 mm. The maximum load for the entire diameter of the bone observed in the experimental group R3.